Clinic-epidemiological characterization and treatment of patients with atrial fibrillation - Frank Miguel Hernández Velazquez; Shannon Elizabeth Carcasés Lamorú; Ramona Lamorú Turro; Alexander Rodríguez Camacho (Revista Cubana de Medicina Militar)
Introduction: Atrial fibrillation was considered for decades as an alternative for sinus rhythm and nowadays it is a severe health problem in many countries of the world associated with some risks factors as cardiac insufficiency, hypertension and diabetes mellitus. It is the most common type of arrhythmia in clinic marks. Objective: Characterize atrial fibrillation in terms of its clinical manifestations and treatment. Development: A bibliographical review was made on published articles from 2010 to 2020. Data Bases like SciELO, EBSCO, PubMed/Medline, Dialnet and open-access magazines were consulted, using the descriptive words atrial fibrillation, supraventricular arrhythmia and reentrance mechanisms for English and Spanish languages. A total of 28 references were selected. In the literature was checked that atrial fibrillation is a supraventricular arrhythmia that can be identified on electrocardiogram by low-amplitude basalts oscillations with an irregular ventricular rhythm. It is produced by unique or multiple reentrance mechanisms that generate a disordered electrical conduction and usually it is accompanied with palpitations, fatigue and dyspnea, but it could also be asymptomatic. Conclusions: Atrial fibrillation has studied clinical signs and treatment is oriented in four directions; frequency controlling, rhythm controlling, thromboembolism prevention and risks factors management.